Analisis Pengendalian Persediaan dengan Metode Economic Order Quantity (EOQ) untuk Meningkatkan Efisiensi Biaya Persediaan Bahan Baku (Studi Kasus pada Maula Hijab Yogyakarta) - Putri, Putri Ratnani; Inna Zahara; David Sulistiyantoro (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2024)
The purpose of this study was to analyze inventory control using the Economic order quantity (EOQ) method to increase the cost efficiency of raw material inventory at Maula Hijab Yogyakarta. This study uses a qualitative approach with data collection methods in the form of interviews, observations, and documentation. The data analysis technique used is a comparative method by comparing the Economic Order Quantity (EOQ) method with the method used by the company to control inventory. The results showed that the application of the Economic Order Quantity (EOQ) method in controlling raw material inventory can minimize the total inventory cost of Rp. 29.713.830 with a total purchase of 84.561 yards each time with a purchase frequency of 6 times. The conclusion of this study shows that the application of the Economic Order Quantity (EOQ) method shows the number of orders that are more economical and can streamline the cost of raw material inventory than the method used by company.